Intestinal Transcriptome Analysis Reveals Enrichment of Genes Associated with Immune and Lipid Mechanisms, Favoring Soybean Meal Tolerance in High-Growth Zebrafish ( Danio Rerio) - Valenzuela, Luis; Pacheco, Sebastian; Rincón, Gonzalo; Pavez, Leonardo; Lam, Natalia; Hernández, Adrián J.; Dantagnan, Patricio; González, Felipe; Jilberto, Felipe; Ravanal, María Cristina; Ramos, Cecilia; García, Héctor; et al. (MDPI, 2021)
The molecular mechanisms underlying fish tolerance to soybean meal (SBM) remain unclear. Identifying these mechanisms would be beneficial, as this trait favors growth. Two fish replicates from 19 experimental families were fed fishmeal-(100FM) or SBM-based diets supplemented with saponin (50SBM + 2SPN) from juvenile to adult stages. Individuals were selected from families with a genotype-by-environment interaction higher (HG-50SBM + 2SPN, 170 ± 18 mg) or lower (LG-50SBM + 2SPN, 76 ± 10 mg) weight gain on 50SBM + 2SPN for intestinal transcriptomic analysis. A histological evaluation confirmed middle intestinal inflammation in the LG- vs. HG- 50SBM + 2SPN group. Enrichment analysis of 665 differentially expressed genes (DEGs) identified pathways associated with immunity and lipid metabolism. Genes linked to intestinal immunity were downregulated in HG fish (mpx, cxcr3.2, cftr, irg1l, itln2, sgk1, nup61l, il22), likely dampening inflammatory responses. Conversely, genes involved in retinol signaling were upregulated (rbp4, stra6, nr2f5), potentially favoring growth by suppressing insulin responses. Genes associated with lipid metabolism were upregulated, including key components of the SREBP (mbtps1, elov5l, elov6l) and cholesterol catabolism (cyp46a1), as well as the downregulation of cyp7a1. These results strongly suggest that transcriptomic changes in lipid metabolism mediate SBM tolerance. Genotypic variations in DEGs may become biomarkers for improving early selection of fish tolerant to SMB or others plant-based diets.
Keywords: RNA-seq.; Soybean meal tolerance.; High-growth fish.; Sustainable aquaculture.; Zebrafish.; Transcriptome.